Evaluation of electrochemical and O3/UV/H2O2 methods at various combinations during treatment of mature landfill leachate. Issue 4 (21st March 2022) - Polatidou, Electra; Azis, Konstantinos; Polatides, Christos; Remmas, Nikolaos; Ntougias, Spyridon; Melidis, Paraschos
Abstract: In this study, electrochemical treatment and application of O3 /UV/H2 O2 in various combinations were evaluated in respect to their efficiency to depurate mature landfill leachate. Based on preliminary experiments, electrochemical treatment using stainless-steel electrodes at 2 cm gap was performed optimally at 50 mA/cm 2 and pH 6, while application of O3 at 120 L/h, UV at 991 J/cm 2 and H2 O2 concentration of 1 g/L was carried out. Electrochemical treatment and O3 /UV/H2 O2 under optimal conditions were applied as follows: I) electrochemical treatment, followed by O3 /UV/H2 O2 and solids precipitation, II) electrochemical treatment, followed by precipitation and then by O3 /UV/H2 O2 treatment, and III) O3 /UV/H2 O2, followed by electrochemical treatment. A low performance was observed when O3 /UV/H2 O2 preceding electrochemical treatment. Solids, TKN and total COD (tCON) removal was primarily achieved through electrocoagulation, whereas color and soluble COD (sCOD) reduction was mainly attributed to electrochemical oxidation. Experimental setup I was the most efficient treatment scheme, resulting in tCOD, sCOD, TKN, TSS, SACUV254nm and color number reduction of 73%, 80%, 76%, 79%, 94% and 98%, respectively. Indeed, O3 /UV/H2 O2 step could be omitted since its effectiveness was restricted during landfill leachate treatment. In conclusion, electrochemical treatment followed by precipitation could result in effective reduction of nutrients and color.